Improving Schools and Schooling in Brazil : The Fundescola Approach - Horn, Robin (World Bank, Washington, DC, 2012)
Public primary schooling in Brazil is the responsibility of state and municipal governments and not under the direct jurisdiction of the federal Ministry of Education. As a consequence, when the federal government wants to improve the quality of schooling, it has neither the mandate nor the capacity to work directly with the country's 184,800 public schools, serving 44 million children. Instead, the Ministry has to mobilize the 27 state-level governments and 5,561 municipal governments to undertake the desired reforms and improvements. The School Improvement Program, designed to address these concerns, consists of three projects. The first, Fundescola I (US$125 million), approved in April 1998, was designed to develop an initial set of school-based instruments and support structures to improve school equity and effectiveness and to increase public awareness around the issue of school quality.. The second project, Fundescola II (US$400 million) , approved in June 1999, focused on improving and expanding the set of tools developed in the first phase, extending these to additional schools, and more aggressively engaging the education establishment and the public sector in the process of school-based development. The third project, Fundescola III, aims at completing the work involved in the development of the tools and processes and scaling these up within Brazil. Fundescola III will be implemented in two phases: Fundescola IIIA (US$320 million), approved on June 13, 2002, and Fundescola IIIB (planned for July 2006, estimated amount US$450 million).